Defining and Measuring Spirituality in South African Specialist Psychiatry - Rensburg, A. B. R. Janse van (Journal of religion and health, 2015)
To define the meaning of “spirituality” in a South African phenomenological, theory-generating qualitative inquiry, theory construction methodology was used. This refers to the tradition of nursing theory development, where a central core concept identified from the integrated data—in this case, interviews and the literature content—had to be defined. A major focus of the study was to distinguish spirituality from religion. The denotative and connotative meanings of “spirituality” were explored to establish the components for a definition. The attributes of this definition included that spirituality constitutes a “quality”, a “journey”, a “relationship” as well as a “capacity”. While these items derived from this local definition of spirituality can be proposed for inclusion in a questionnaire for measuring spirituality in a South African context, the limits of the scope of the explorative qualitative inquiry from which it was derived must be considered.